Si-doped AlN using pulsed metalorganic chemical vapor deposition and doping - Tariq Jamil; Abdullah Al Mamun Mazumder; Mafruda Rahman; Muhammad Ali; Jingyu Lin; Hongxing Jiang; Grigory Simin; Asif Khan (Applied Physics Express)
In this paper we describe a pulsed metalorganic chemical vapor deposition (MOCVD) Si-doping approach for AlN epilayers over bulk AlN. The Al-rich growth/doping conditions in the pulsed MOCVD process resulted in n-AlN layers with transmission line model currents that were an order higher than for structures on layers that were grown/doped at identical temperatures using the conventional MOCVD process. Our work demonstrated that like the other reported approaches such as UV exposure during growth, the pulsed MOCVD process is also very effective in reducing point defects by the defect quasi-Fermi level-chemical potential control.